Roadside Abundance of Anurans within a Community Correlates with Reproductive Investment - Grace, Molly K.; Smith, Daniel J.; Noss, Reed F. (Frontiers in Ecology and Evolution, 2017)
Roads and their associated effects (road-kill, pollution, etc.) have a largely negative impact on animals, especially amphibians, but not all species are affected to the same degree. Variation in life histories may explain some of these differences. Here, we examine how abundance of anuran species in roadside habitats is correlated with an aspect of reproductive life history: number of eggs produced by a female per year. Using data from a 1.5-year monitoring project in Central Florida, we found a positive correlation between the number of eggs produced by an average female of a species and the proportion of individuals found in roadside habitats compared to control habitats. This implies either that populations of species with a greater reproductive rate are able to rebound more quickly from negative road impacts, or that there is a strong selective pressure on species with low reproductive rates to avoid roads.